Institusi Dakwah di Cape Town, Afrika Selatan: Kajian Tentang Program Dakwah Masakini - Mohd. Zin, Ab. Aziz (Jurnal Usuluddin, 1999)
Part II of the da'wah development in Cape Town and its survival nowadays describes the activities of da'wah which have been made by Islamic institutions in Cape Town. It also introduces the institutions involved and their problems. These activities continuously strengthen Islam in Cape Town although it always has to face many problems. These excellent efforts are the pride of the Muslims of the world, especially the Islamic community of the Malay Archipelago.